KELANGSUNGAN HIDUP DAN PERTUMBUHAN LARVA IKAN SELAIS (Kryptopterus lais) YANG DIBERI CACING SUTERA (Tubifex tubifex) UTUH DAN OLAHAN - Agusnimar Agusnimar; Sholihin Sholihin; Abdul Fatah Rasyidi (DINAMIKA PERTANIAN, 2015)
An experiment was conducted to evaluate the survival and growth of Kryptopteruslais larvae given fed intact and processed T. tubifex. Fish larvae used in this experiment waslarval of Kriptopterus lais 7 days old, while initial mean weigh and length of larvae were 0,002 g and 0,7 cm, respectively. The experiment used in this study was the completely randomized design, with three treatments and three replications; P1 (intact T.tubifex); P2 (Minced T.tubifex), and P3 (T. tubifex in blender). The results showed that there was no significant difference across treatments for survival rate and growth rate of Kryptoterus lais larvae (P > 0.05). The highest survival rate (38.27%) was recorded in P1(intract T.tubifex). In Addition, the highest weight (0.513 gr) and length (3.93 cm) of K. lais larvae were also found in P1.